Age‐independent myocardial infarct quantification by signal intensity percent infarct mapping in swine. Issue 4 (10th September 2015) - Lenkey, Zsofia; Varga‐Szemes, Akos; Simor, Tamas; van der Geest, Rob J.; Kirschner, Robert; Toth, Levente; Bodnar, Tamas; Brott, Brigitta C.; Elgavish, Ada; Elgavish, Gabriel A.
Abstract : Purpose: To test whether signal intensity percent infarct mapping (SI‐PIM) accurately determines the size of myocardial infarct (MI) regardless of infarct age. Materials and Methods: Forty‐five swine with reperfused MI underwent 1.5T late gadolinium enhancement (LGE) magnetic resonance imaging (MRI) after bolus injection of 0.2 mmol/kg Gd(DTPA) on days 2–62 following MI. Animals were classified into acute, healing, and healed groups by pathology. Infarct volume (IV) and infarct fraction (IF) were determined by two readers, using binary techniques (including 2–5 standard deviations [SD] above the remote, and full‐width at half‐maximum) and the SI‐PIM method. Triphenyl‐tetrazolium‐chloride staining (TTC) was performed as reference. Bias (percent under/overestimation of IV relative to TTC) of each quantification method was calculated. Bland–Altman analysis was done to test the accuracy of the quantification methods, while intraclass correlation coefficient (ICC) analysis was done to assess intra‐ and interobserver agreement. Results: Bias of the MRI quantification methods do not depend on the age of the MI. Full‐width at half‐maximum (FWHM) and SI‐PIM gave the best estimate of MI volume determined by the reference TTC ( P ‐values for the FWHM and SI‐PIM methods were 0.183, 0.26, 0.95, and 0.073, 0.091, 0.73 in Group 1, Group 2, and Group 3, respectively), while using any of the binary thresholds of 2–4 SDs above the remote myocardium showed significant overestimation. The 5 SD method, however, provided similar IV compared to TTC and was shown to be independent of the size and age of MI. ICC analysis showed excellent inter‐ and intraobserver agreement between the readers. Conclusion: Our results indicate that the SI‐PIM method can accurately determine MI volume regardless of the pathological stage of MI. Once tested, it may prove to be useful for the clinic. J. Magn. Reson. Imaging 2016;43:911–920